Developing Islamic Religious Education (PAI) Learning Methodology through Information Processing Theory - Norma Yulianti; Tri Miratul Hasanah; Ayu Wulandari; Bima Wisnu Gunawan; Siti Roudhotul Jannah (CV. Creative Tugu Pena, 2025)
This study aims to develop a learning methodology for Islamic Religious Education (PAI) based on the principles of Information Processing Theory. The research is motivated by the need to enhance the effectiveness of PAI instruction so that it aligns more closely with learners’ cognitive characteristics, particularly in processing, storing, and interpreting religious information. Using a library research approach, this study analyzes literature on information processing theory, instructional methodologies, and PAI learning practices. The findings indicate that applying Information Processing Theory in PAI learning can be achieved through strategies such as activating prior knowledge, organizing instructional content using concept maps, utilizing media that support both visual and verbal memory, and assessing students’ thinking processes through elaboration and reflection techniques. The proposed methodology has been shown to strengthen conceptual understanding, improve long-term retention, and enhance students’ critical thinking skills. The study concludes that integrating Information Processing Theory into PAI instruction offers a relevant and effective methodological alternative for improving the quality of PAI learning across educational levels.